Students’ Perceptions of Formative Assessment in English Classes - Lelyta Maeyasningrum; Sarlita Dewi Matra (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study explores eleventh-grade students’ perceptions of formative assessment in English language learning. Formative assessment is widely recognized as a strategy that enhances student engagement, reflection, and understanding. Using a qualitative approach, data were collected through a closed-ended questionnaire based on a Likert scale. Fourteen students from Senior High School 1 Wiradesa participated in the study during the 2024/2025 academic year. The results indicate that students generally held positive to very positive views of formative assessment. Key aspects contributing to this perception included timely teacher feedback, active classroom discussions, and the integration of digital tools. Students also reported that formative assessment boosted their confidence, deepened their understanding of the material, and helped them feel more prepared for exams. Overall, the study highlights the crucial role of formative assessment in creating a learning environment that is interactive, reflective, and responsive to students’ needs.